Soil Settlement and Tunnel Deformations Pattern Analysis of Underground Single Tunnel MRT Putrajaya Line Using Finite Element Method - Azhar, Syaibatul Nur Eizzaniq; Abd Latif , Muhamad Faiz; Mohd Sukarno, Ahmad Syazwan; Gopalan , Thanath (Progress in Engineering Application and Technology, 2022)
As the growth of Kuala Lumpur conurbation expands, traffic congestion and pollution are the two significant problems in many urban areas. A significant segment of KL’s population wants an option. By integrating many existing rail networks, MRTC can increase rail transportation opportunities by providing a premium quality service at a reasonable fare. The Putrajaya Line is the second line of the KVMRT Project after Kajang Line operated. The underground alignment of the PY line traversed through Kuala Lumpur Limestone, Granite and Kenny Hills Formation. The process of tunnel excavation will cause a disturbance to the surrounding soil, which is unavoidable. An engineer must observe the behavior of soil that would cause ground movement during tunnel excavation. To predict the ground behavior, the development of the Finite Element Method comes as an alternative solution. To design the tunnel and soil modelling using PLAXIS 2D version 2022 to see the output of settlement and tunnel deformed. There are three key parameters to see the effect of surface settlement and tunnel deflection: tunnel depth, groundwater level and soil stiffness. To conclude the analysis result, the three key parameters give impact to the surface settlement and tunnel deflection. However, at certain level, the settlement and tunnel deflection are at average because the sensitivity of soil are decreasing. This research is necessary for understanding the impact of surface settlement due to ground movement on the underground tunnel.